Parameters of Stromal Activation and Epithelial to Mesenchymal Transition as Predictive Biomarkers for Induction Chemotherapy in Patients With Locally Advanced Oral Cavity and Oropharyngeal Squamous Cell Cancer - Geweiler, Jana (Clin Exp Otorhinolaryngol, 2016)
OBJECTIVES: Induction chemotherapy (IC) is likely to be effective for biologically distinct subgroups of oral cancer and biomarker development may lead to identification of those patients. METHODS: We evaluated immune cell infiltration, stroma formation and structure of the invasive front as well as the immunohistochemical expression of alpha smooth muscle actin (ASMA), CD163, E-cadherin, N-cadherin, and the laminin gamma 2 chain in pretreatment biopsy specimens and surgical resections after IC in 20 patients with locally advanced oral cancer who were treated in a prospective, ongoing, phase II trial on IC using docetaxel, cisplatin, and 5-fluorouracil (TPF). RESULTS: Significant negative prognostic factors for incomplete pathological tumor response to IC were alcohol abuse (P=0.032), cN+ (P=0.042), and <30% tumor reduction after first cycle of IC (P=0.034). Of the investigated histological parameters and biomarkers only a low membrane-bound expression of E-cadherin showed a trend to be associated with incomplete response to IC (P=0.061). Low expression of ASMA in stromal vessels and a strong tumor invasion front were significantly associated to tumor recurrence (P=0.024 and P=0.004, respectively). The median follow-up of all patients was 35 months. Alcohol abuse (P<0.001), <30% tumor reduction after first cycle of IC (P=0.005), and a strong tumor invasion front (P=0.019) were negative prognostic factors for overall survival. CONCLUSION: A strong predictive biomarker among the investigated parameters for benefitting from TPF IC could not be found. The extent of the tumor invasion front was a negative prognostic marker for recurrence and survival in oral cancer treated by TPF IC followed by surgery and postoperative radiochemotherapy.